2009
DOI: 10.1007/s10578-009-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Behavioral Performance of Internationally Adopted Preschoolers: A Pilot Study

Abstract: Most international adoptees (IA) have rapid catch-up of the delays common at arrival. However, it is not known whether development at arrival predicts later abilities or school readiness. Therefore, we comprehensively evaluated language, fine motor, visual reception (VR), executive function (EF), attention (ATT), and sensory skills (SS) in IA preschoolers. We hypothesized that pre-adoptive risk factors, development at arrival, and the post-adoptive environment (time in day care) would predict developmental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 53 publications
4
61
1
2
Order By: Relevance
“…The existence of a higher presence of attention problems and hyperactivity among internationally adopted children compared to the general population has been suggested by several authors (Simmel, Brooks, Barth, & Hinshaw, 2001;Jacobs, Miller, & Tirella, 2010;Lindblad , Ringbäck Weitoft, & Hjern, 2010). In this regard, our results showed that the scores for the Hyperactivity and Attention problems scales obtained by the group of children adopted from Ethiopia and Eastern Europe were higher than expected, but lower for the group of girls adopted from China.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The existence of a higher presence of attention problems and hyperactivity among internationally adopted children compared to the general population has been suggested by several authors (Simmel, Brooks, Barth, & Hinshaw, 2001;Jacobs, Miller, & Tirella, 2010;Lindblad , Ringbäck Weitoft, & Hjern, 2010). In this regard, our results showed that the scores for the Hyperactivity and Attention problems scales obtained by the group of children adopted from Ethiopia and Eastern Europe were higher than expected, but lower for the group of girls adopted from China.…”
Section: Discussionsupporting
confidence: 73%
“…"Significant problem" scores for hyperactivity were found for 14% of children and Attention regulation parameters scored as "atypical" for inattention, hyperactivity and ADHD traits, respectively in 26, 42 and 28% of the children (Jacobs, Miller, & Tirella, 2010). In the same study, the age at arrival was found to be a very strong predictor of many of the outcome measures tested, including Hyperactivity and Attention deficit, with children who were younger at arrival scoring better in each of these areas.…”
Section: Adhd Symptoms In Internationally Adopted Childrenmentioning
confidence: 70%
See 1 more Smart Citation
“…The only studies of EF in preschool PI children used parent report to assess EF problems using the Behavior Rating Inventory of Executive Function Preschool Version (BRIEF-P) and reported mixed results. One study found no differences compared with a normative sample in adopted preschool children aged 2-5 y (14), whereas another found that 11% of children aged 4-5 y had EF problems in the clinical range according to parent ratings (34). The third study did not include a comparison group (35); thus, the authors were only able to conclude that parents of PI children reported more EF problems than teachers did.…”
Section: Ef In Postinstitutionalized Childrenmentioning
confidence: 98%
“…Hubel and Wiesel were among the first to document the important effects of early experience (eg, deprivation) on the way visual sensory input is processed in the brain. [2][3][4][5] Animal and human research is beginning to explore how other senses are processed and integrated [6][7][8][9][10] and how those processes are disrupted in specific syndromes (eg, autism, 11,12 schizophrenia 13,14 ) and by specific experiences (eg, institutionalization, international adoption 15,16 ).…”
mentioning
confidence: 99%